2001
DOI: 10.1111/j.1600-0609.2001.00272.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon alfa 2b as maintenance therapy
in poor risk diffuse large B‐cell lymphoma in complete remission after intensive CHOP–BLEO regimens

Abstract: Objectives: We conducted a randomized clinical trial to evaluate the role of interferon alfa 2b (IFN) as maintenance therapy in patients with diffuse large B‐cell lymphoma with high or high–intermediate clinical risk on complete remission (CR) after CHOP–BLEO regimens. Methods: Patients were initially treated with CHOP–BLEO regimens (which include increased doses of cyclophosphamide and epirubicine, instead of doxorubicin). If the patients achieved CR they were randomly assigned to receive either maintenance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…[10][11][12] The trials were conducted between the years 1981 and 2017. 2,[10][11][12][13][14][15][16][17][18][19][20][21][22] The characteristics of the trials are shown in Table 1.…”
Section: Description Of Trialsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10][11][12] The trials were conducted between the years 1981 and 2017. 2,[10][11][12][13][14][15][16][17][18][19][20][21][22] The characteristics of the trials are shown in Table 1.…”
Section: Description Of Trialsmentioning
confidence: 99%
“…In 6 trials, only patients with intermediate-high and high-risk international prognostic index (IPI) or age-adjusted IPI were included. 10,12,13,[19][20][21] In 4 trials, patients with any IPI were included. [15][16][17][18] IPI score was not mentioned in 4 trials.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they suggested that R cannot be employed in this clinical situation. 13,14 Maintenance therapy has been employed after induction regimens in DLBCL and has used low doses of cytotoxic drugs, 15 interferon after standard CHOP, 16 and with the use of intensive or dose-dense regimens, [17][18][19] induction of graftversus-host disease, 20 SCT after CHOP or R-CHOP 21 ; however, no clear benefit has observed. On the other hand, late toxicities continue to be a problem that can be intensified with the use of maintenance therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Female patients represented 65% of our study, with male to female ratio1:1.8. Opposite to data from IFN and Rituximab maintenance trials were the majority of patients were males (52% in CHOP-R arm in the first trial and 55% in the second trial) 14,17 .…”
Section: Rituximab In Diffuse Large B Cell Lymphomamentioning
confidence: 91%